Pokémon adventures. Diamond and Pearl platinum. 08 - Kusaka, Hidenori (Viz Media, 2013)
"To prepare for their big battle, our trio of friends each need to reach out for help--from Gym Leaders to new Pokémon. Then Lady, Pearl and Diamond are finally reunited in the very heart of Team Galactic's headquarters. Can they release the three Legendary Pokémon...before it's too late? And who will take on Team Galactic's powerful leader Cyrus?!"--P. [4] of cover.